An Epic Poem at the Court of Leonello d’Este: Basinio da Parma’s “Meleagris” (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2023)
This paper’s aim is to investigate the epic literature produced in Ferrara in the generation before Boiardo, using Basinio da Parma’s poem Meleagris (1448) as a case study. The main focus is on its narrative aspects, analysed on the basis of a comparison with the poem’s direct source, i.e. the passage from Ovid’s Metamorphoses centred on the Calydonian boar hunt. Two guiding lines of Basinio’s narrative technique are identified: the implementation of the structural complexity of the work (the result of a threefold will to increase the pathos of the narration, to achieve an aemulatio of the model and to introduce an encomiastic exaltation of the lord) and the amplification of the peculiar features of the Ovidian text, namely those passages that undermine the epic register. It is therefore highlighted the presence in nuce, already in this phase of Ferrarese literature, of a marked narrative sensibility, which still coexists with fully humanistic forms of classical imitatio.
Keywords: Humanism; Ferrara; Epic poetry; Basinio da Parma; Meleager; Ovid; Narrative Techniques